The Role of Digitalization in the Scientific and Educational Space Integration of the EAEU - C. G. Gospodarik; M. M. Kovalev (Цифровая трансформация)
The article analyzes the modern potential of education and science in the EAEU countries for the rapid and effective implementation of high-tech import substitution, and also builds econometric models of the impact of education and science on GDP growth on two panels and historical data for 1990-2020 for developed and developing countries, with their subsequent application to assess the impact of the unified scientific and educational space of the EAEU on economic growth with the identification of the main factors of such influence, which made it possible to formulate the most promising ways and mechanisms for creating a unified scientific and educational space of the EAEU.